2012
DOI: 10.1177/1082013211428014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quality Index Method for anchovy (Engraulis anchoita) stored in ice: Assessment of its shelf-life by chemical and sensory methods

Abstract: The objective of this study was to develop a quality index method for Engraulis anchoita stored in ice and to determine its shelf-life based on this quality index method and chemical indices such as total volatile bases and thiobarbituric acid-reactive substances. Besides, the chemical composition with emphasis on the polyunsaturated fatty acids content was determined. The results indicate that E. anchoita is a valuable protein source and lipid with important content of n-3 polyunsaturated fatty acids. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 63 publications
5
21
0
Order By: Relevance
“…The total points sum (Quality Index) reached 19 demerit points at rejection (Table 1) fish. This value is similar to those found for the Argentine anchovy Engraulis anchoita, where values found by other authors was between 0.43 to 1.66 (del Valle et al, 1984;Capaccioni et al, 2011;Massa et al, 2012). Nunes et al (1992) observed that the concentration of TBARS in fresh fish is typically between 3 and 5 mg MA/kg.…”
Section: Development Of the Qim Scheme For Common Carpsupporting
confidence: 89%
See 3 more Smart Citations
“…The total points sum (Quality Index) reached 19 demerit points at rejection (Table 1) fish. This value is similar to those found for the Argentine anchovy Engraulis anchoita, where values found by other authors was between 0.43 to 1.66 (del Valle et al, 1984;Capaccioni et al, 2011;Massa et al, 2012). Nunes et al (1992) observed that the concentration of TBARS in fresh fish is typically between 3 and 5 mg MA/kg.…”
Section: Development Of the Qim Scheme For Common Carpsupporting
confidence: 89%
“…In general, sensory tables do not include parameters that involve the cutting of fish in order to preserve their commercial value, so that destructive parameters are normally avoided (Sveinsdóttir et al, 2003;Bekaert, 2006;Massa et al, 2012;Badiani et al 2013). Destructive parameters also involve delays in sample preparation and evaluation and require the use of specially-dedicated facilities, resulting in more time-consuming and less practical determinations.…”
Section: Development Of the Qim Scheme For Common Carpmentioning
confidence: 99%
See 2 more Smart Citations
“…The shelf life of fish shelf life can be determined by physicochemical and microbiological analysis, as well as, sensory changes that occur in fish during the storage period have been commonly used (Massa et al, 2012, Borges et al, 2013and Giuffrida et al, 2013.…”
Section: Introductionmentioning
confidence: 99%